(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper analyses changes in legislation regarding the commitment of persons suffering from mental illness in the Spanish legal system, which has evolved frombeing largely an administrative proceeding to a proceeding subject to rigorous legalcontrols. Psychiatric commitment, as a therapeutic measure, affects the fundamental right to freedom. For this reason, the provisions in the Spanish Constitution of 1978,international instruments on this matter and fundamentally the 1950 European Convention for the Protection of Human Rights and Fundamental Freedoms as wellas case law developed by the European Court of Human Rights must be taken into account. This paper examines applicable legislation, doctrine and legal precedents.The analysis reveals the significant legislative progress that has been made in the regulationof psychiatric commitments and points out some unresolved issues in this area.